How to build a human : in seven evolutionary steps - Turner, Pamela S. (Charlesbridge, 2022)
Explores human evolution, from our primate ancestors to Homo sapiens, through seven steps including walking on two legs, the creation of toolmaking, the development of larger and more complex brains, the migration of Homo erectus out of Africa, the shift from raw to cooked foods, the evolution of human language, and the advent of storytelling. Includes photographs, illustrations, diagrams, maps, a timeline, a glossary, and additional resources.